Sticky prices and moderate inflation (2008)
Recent evidence shows that there is great heterogeneity in the price setting frequency across sectors, and that those changing prices frequently do so even under low inflation. What happens to price setting strategies of sticky price goods under moderate inflation? We built a dataset of monthly newspaper and magazine prices for Colombia, for the period 1960-2005, an exceptional example of prolonged moderate inflation. Within this macroeconomic scenario, and the novel database, we study the frequency of price adjustment, the relative importance of time- and state-dependent theories, and their evolution as inflation declined from moderate rates to single digits.